EVEKTIVITAS PERMAINAN TRADISIONAL BAREN TERHADAP HASIL BELAJAR LARI SPRINT 100 METER PADA SISWA PUTRA KELAS VIII MTs MA’ARIF SUKANAGARA TAHUN PELAJARAN 2022/2023 - N. Siti Nuraeni Sofa; Mirwan Aji Soleh (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The results of learning to run short distances are less developed, especially in the 100 meter number. One of the causes, according to the results of direct observation conducted by the author on male students of Class VIII MTs Ma'arif Sukanagara, Darmaraja District, Sumedang Regency, is the situation and conditions of physical education learning itself, it seems that students in general lack varied and challenging learning experiences. Based on the findings in the field and at the same time the solution to this problem, the author wants to try to improve the learning outcomes of short distance running in the form of a game so that students' motivation to learn is maintained. One form of the game that the author will apply is the traditional baren game,